Seismic Performance Evaluation Of Building Structures Modified With Special Concentrically Braced Frames (SCBF) - Septiarsilia, Yanisfa; Susanti, Eka; Fitriyah, Dita Kamarul; Dewi Pertiwi; Umbu Miron (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2026)
The Concentrically Braced Frame (CBF) system utilizes diagonal steel bracing members to enhance structural stiffness and dissipate seismic energy, thereby reducing potential damage to primary structural elements. CBF systems are classified into Special Concentrically Braced Frames (SCBF) and Ordinary Concentrically Braced Frames (OCBF), which are applied in high and moderate-to-low seismic regions, respectively. This study evaluates the modification of an existing 13-story hotel building into an SCBF system in accordance with the latest Indonesian seismic design provisions. The research methodology includes a literature review on SCBF design principles and the most recent SNI standards, preliminary design, numerical modeling, and dynamic analysis using SAP2000. The structural behavior parameters evaluated in this study include mass participation, fundamental period (time period), and interstory drift. The results indicate that both the existing structure with a Dual System (SMRF and shear wall) and the SCBF-modified structure satisfy the minimum 90% mass participation requirement specified in SNI 1726:2019, with the SCBF system achieving this criterion using fewer vibration modes. However, the evaluation of the fundamental period shows that the existing structure remains within the allowable code limits, whereas the SCBF-modified structure exceeds the maximum permitted fundamental period, indicating increased structural flexibility and insufficient lateral stiffness. In terms of interstory drift performance, both structural systems comply with the drift limits specified in SNI 1726:2019; nevertheless, the Dual System demonstrates superior lateral deformation control compared to the SCBF system. Therefore, it can be concluded that the structural modification using the SCBF system in this study was not successful in replacing or outperforming the existing Dual System. Although the SCBF configuration meets certain code requirements, it does not provide adequate lateral stiffness nor improved seismic performance compared to the original structural system.